The molecular mechanism of the anticancer effect of Artonin E in MDA-MB 231 triple negative breast cancer cells - Etti, Imaobong Christopher; Abdullah, Rasedee; Kadir, Arifah; Hashim, Najihah Mohd; Swee, Keong Yeap; Imam, Mustapha Umar; Ramli, Faiqah; Malami, Ibrahim; Kian, Lim Lam; Etti, Ubong; Waziri, Peter; Rahman, Marsitoh (Public Library of Science, 2017)
Nature has provided us with a wide spectrum of disease healing phytochemicals like Artonin E, obtained from the root bark of Artocarpus elasticus. This molecule had been predicted to be drug-like, possessing unique medicinal properties. Despite strides made in chemotherapy, prognosis of the heterogenous aggressive triple negative breast cancer is still poor. This study was conducted to investigate the mechanism of inhibition of Artonin E, a prenylated flavonoid on MDA-MB 231 triple negative breast cancer cell, with a view of mitigating the hallmarks displayed by these tumors. The anti-proliferative effect, mode of cell death and the mechanism of apoptosis induction were investigated. Artonin E, was seen to effectively relinquish MDA-MB 231 breast cancer cells of their apoptosis evading capacity, causing a half-maximal growth inhibition at low concentrations (14.3, 13.9 and 9.8 μM) after the tested time points (24, 48 and 72 hours), respectively. The mode of cell death was observed to be apoptosis with defined characteristics. Artonin E was seen to induce the activation of both extrinsic and intrinsic caspases initiators of apoptosis. It also enhanced the release of total reactive oxygen species which polarized the mitochondrial membrane, compounding the release of cytochrome c. Gene expression studies revealed the upregulation of TNF-related apoptosis inducing ligand and proapoptotic genes with down regulation of anti-apoptotic genes and proteins. A G2/M cell cycle arrest was also observed and was attributed to the observed upregulation of p21 independent of the p53 status. Interestingly, livin, a new member of the inhibitors of apoptosis was confirmed to be significantly repressed. In all, Artonin E showed the potential as a promising candidate to combat the aggressive triple negative breast cancer.